2006
DOI: 10.3892/ijo.29.5.1295
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids induce chemotherapy resistance in the majority of tumour cells from bone, brain, breast, cervix, melanoma and neuroblastoma

Abstract: Glucocorticoids (GCs) such as dexamethasone (DEX) have been widely used as co-medication in cancer therapy because they have potent proapoptotic properties in lymphoid cells, can reduce nausea, and alleviate acute toxic effects in healthy tissue. However, GCs are used in a supportive-care role, even though no prospective clinical studies have assessed the effect of these steroids on the growth of solid tumours. Data from preclinical and, to some extent, clinical studies, suggest that GCs induce treatment resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 16 publications
2
56
1
1
Order By: Relevance
“…To our knowledge, the present in vitro study was the first to address this question, and it is reassuring that our results showed, in the majority of dexamethasone drug concentrations and time-points studied, no inhibition of the cytotoxic activity of cetuximab suggesting no evidence for an adverse interaction between cetuximab and dexamethasone in head and neck cancer cell lines. So these findings are partially in contrast to those reported by Zhang et al (19) who demonstrated glucocorticoid-induced resistance to chemotherapy in the majority of cell lines derived from various malignancies including brain, breast, cervix, melanoma and neuroblastoma. Gassler et al (14) found an anti-apoptotic effect of glucocorticoids in tissue samples from lung cancer.…”
Section: Discussioncontrasting
confidence: 56%
“…To our knowledge, the present in vitro study was the first to address this question, and it is reassuring that our results showed, in the majority of dexamethasone drug concentrations and time-points studied, no inhibition of the cytotoxic activity of cetuximab suggesting no evidence for an adverse interaction between cetuximab and dexamethasone in head and neck cancer cell lines. So these findings are partially in contrast to those reported by Zhang et al (19) who demonstrated glucocorticoid-induced resistance to chemotherapy in the majority of cell lines derived from various malignancies including brain, breast, cervix, melanoma and neuroblastoma. Gassler et al (14) found an anti-apoptotic effect of glucocorticoids in tissue samples from lung cancer.…”
Section: Discussioncontrasting
confidence: 56%
“…2). Additionally, CDDP and 5-FU induced apoptosis, whereas the inhibition of apoptosis by DEX promoted proliferation in various established and primary cancer cells (12). The enhanced secretion of Cys C induced by co-treatment with DEX might be correlated with the inhibition of apoptosis as well as the abovementioned transcriptional regulation.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9][10][11][12][13] There have been conflicting results concerning the antitumor effects of GCs. In some tumors, GCs assist tumor progression by inhibiting chemotherapy-induced or immunoresponse-induced apoptosis, promoting tumor growth 24 and increasing cancer invasiveness. [25][26][27] Conversely, GC induces tumor apoptosis by negatively affecting the transcription of nuclear factor kappaB (NF-jB ), an important regulator of the immune system and antiapoptotic mechanisms, in various cell lines and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%